Harry Potter, a teenage conspiracy myth - Julien CUEILLE (Sociopoétiques)
The Harry Potter series of novels (1997-2007) by J. K. Rowling features a teenage protagonist who is pursued by a group of conspiring wizards who want to kill him and seize power. But Harry himself is a member of a secret society that resorts to conspiracy. And another reading might see in Harry a young man who shares many traits with certain contemporary adolescents, particularly the search for self, narcissistic flaws and interest in fictional plots. This article examines the articulations and issues of these different forms of conspiracy in J. K. Rowling’s successful work. On the basis of the (socio-)anthropological and psychoanalytical representations that inform it, it shows that the imagination of conspiracy that fuels the journey of Harry Potter gives it a mythical dimension that allows its many readers to achieve self-learning.